L'évolution du système consonantique des langues cangin - Drolc, Ursula (AAeO - Afrikanistik-Aegyptologie-Online, 2006)
The Cangin languages are classified as an own subgroup of the Atlantic languages. Evidence for their common origin can be given by the comparative method. By means of the systematic grammatical comparison of different languages this method aims at the reconstruction of a hypothetic proto-language and allows to draw hypothesises on their diachronic linguistic development. This paper concentrates on the evolution of the consonant system of the Cangin languages.